Selenium and Omega-3 Fatty Acids Ameliorate Highly Active Anti-Retroviral Therapy (HAART)-induced Reproductive Impairment in Male Wistar Rats (Nigerian Journal of Physiological Sciences, 2023)
Highly active anti-retroviral therapy (HAART) is currently the main stay in the treatment of Human Immunodeficiency Virus (HIV) disease. This treatment regimen typically combines three or more antiretroviral drugs and like most drug combinations or polypharmacy, has side effects including those on reproductive function which could place HIV patients on HAART under double risk in terms of reproductive function. Part of tissue damage following HAART administration is blamed on oxidative stress. We therefore sought to explore effects of Omega 3 and Selenium, two common antioxidants on HAART-induced male reproductive impairment in a non-HIV animal model. Sixteen male adult Wistar rats weighing 120g to 250g used for the study were grouped into 4 groups of four rats each (control, HAART-only, HAART + Omega 3 and HAART + Selenium groups). Duration of daily administration was six weeks. Results showed no significant changes in pH of epidydimal semen among the groups. Sperm count and viability were significantly reduced in HAART-only compared with control (p